Corporate green initiatives and financial performance in Malaysian plantation sector - Wang, Xin Rui; Mohd Said, Ridzwana; Kamarudin, Fakarudin; Abdul Rahim, Norhuda (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Adoption of green initiatives by companies is important to create healthier environment. Added with the demand from wider stakeholders, companies realise the importance of disclosing information in their corporate report. The purpose of this study is to examine the effect of green initiatives on companies’ performance of plantation sector in Malaysia. Twenty-one public listed companies were selected. Content analysis was used to collect data from annual reports and sustainability reports related to information on green product, wastewater treatment technologies and energy efficiency. Data for dependent variables which are return on asset and return on equity also were obtained from annual reports. Descriptive analysis, correlation analysis and multiple regressions using SPSS were adopted to analyse the data. The results of this study reveal that energy efficiency have significant relationship with companies’ financial performances whereas green product and wastewater treatment technologies show in contrary.